Analyzing effects of green marketing mix towards brand image and purchase decision of starbucks - Mumtaz, Muhammad Hauzan Refin; Hudrasyah, Herry (Journal of Business and Management, 2020)
Abstract. Every year public awareness increases toward the problem of plastic waste in Indonesia. Several company quickly accepted eco-friendly concepts, such as an environmental management system and waste minimization, and has also integrated environmental problems in all company activities. One of the companies that is already concerned about the plastic waste problem is Starbucks. Starbucks sells many eco-friendly items in their store and uses green marketing mix strategies which aim to make a positive brand image and generated purchase decisions. Despite the prospect of green consumers who are aware of environmental problems, by implementing green marketing mix the company is also constrained by financial problems because the cost of implementing green marketing mix is more expensive. This research aims to analyze the effect of green marketing mix towards brand image and purchase decision of Starbucks. The research was conducted using a quantitative approach to 351 respondents and the data will be analyzed using PLS- SEM method. The finding from this result shows that green marketing mix has a positive impact on brand image and purchase decision. Outcomes from this research expected can give insight to Starbucks and other companies that implemented green marketing mix to maintain the green marketing mix that has been done and find new innovations regarding green marketing mix.Â Keywords: green marketing, brand image, purchase decision, structural equation modeling